PENGARUH MEDITASI CINTA KASIH DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR SISWA PENDIDIKAN AGAMA BUDDHA DI SMK NEGERI 1 TANJUNG KABUPATEN LOMBOK UTARA - Joni Pranata; Suherman, Suherman; Julia surya (LPSDI Bina Patria, 2024)
Learning outcomes are one of the indicators of achieving educational goals, to overcome the achievement of learning outcomes that are less than optimal, SMK Negeri 1 Tanjung North Lombok Regency has implemented the practice of loving kindness meditation and self-confidence in an effort to increase student learning concentration. The problem in this study based on preliminary observations shows that not a few students of SMK Negeri 1 Tanjung still show symptoms of lack of concentration and lack of confidence in learning. Data collection was carried out on the population that had been established by the researcher with questionnaires. The collected data is tested for validity and reliability, which is analyzed using inferential statistical methods. The results of the analysis are presented in the form of tables, frequency distribution tables, and graphs. Next, discussion and interpretation are carried out. Finally, conclusions are made based on the data collected as a short answer to each problem formulation that has been proposed. The results showed that the regression of loving-kindness meditation (X1) had an effect of 0.751 or 75.1%, the regression of the Self-Confidence variable (X2) of -0.216, this showed that the level of self-confidence carried out on students of SMK Negeri 1 Tanjung North Lombok Regency was very low but very significant. Simultaneously Loving Kindness Meditation, Self-Confidence has a positive and significant effect on Learning Outcomes at SMK Negeri 1 Tanjung North Lombok Regency. Based on the results of the coefficient of determination test, an Adjusted R Square value of 0.183 was obtained. These results showed that only 18.3% of the variables of loving-kindness meditation (X 1), self-confidence (X2) were able to explain the variable of learning outcomes (Y) in students of SMK Negeri1 Tanjung North Lombok Regency while the remaining 81.7% were the influence of other independent variables that were not explained. Based on the results of the study, it can be concluded that the loving kindnes meditation and self-confidence of students shows a significant influence on the learning outcomes of SMK Negeri 1 Tanjung students. The suggestion put forward is that loving kindness meditation and self-confidence need to be further improved by students, so that its application does not only stop at school, but can be continued at home, and other researchers are advised to conduct more in-depth similar research on loving kindness meditation and students’ self confidence